2014
DOI: 10.1590/0004-282x20140155
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ quality of life in mild and moderate dementia

Abstract: Objective: To investigate quality of life (QoL) of caregivers of mild and moderate dementia and the aspects related to QoL. Method: Crosssectional assessment of dyads of people with dementia (PwD) and family caregivers (n=88). Results: Burden (p,0.05) and depressive symptoms (p,0.001) were related to caregivers' QoL in both stages of dementia. In mild dementia, caregivers' depressive symptoms (p,0.001) and PwD neuropsychiatric symptoms (p,0.001) were related to burden. PwD aberrant motor activity (p,0.001) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 18 publications
7
37
0
10
Order By: Relevance
“…As in both the groups, caregivers were exposed to continuous psychological and emotional trauma in the chronic course of both the diseases, so quality of life was deteriorated. 25 The most important finding of this study was negative correlation between family burden and quality of life of caregivers in both the groups. In dementia caregiver group, it was observed that with increase in caregivers' family burden resulted in poor functioning of psychological, environmental and social relationship domains of quality of life.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As in both the groups, caregivers were exposed to continuous psychological and emotional trauma in the chronic course of both the diseases, so quality of life was deteriorated. 25 The most important finding of this study was negative correlation between family burden and quality of life of caregivers in both the groups. In dementia caregiver group, it was observed that with increase in caregivers' family burden resulted in poor functioning of psychological, environmental and social relationship domains of quality of life.…”
Section: Discussionmentioning
confidence: 53%
“…In case of caregivers of schizophrenia, the psychological domain of quality of life was affected as the family burden increases, because of stigma, discrimination and variations in the course of the disease. 25,26 The key caregivers during their caring for the chronic psychiatric patients have subjective experiences of anger, fear, dependency, incompetency, embarrassment, expectation and uncertainty. This burden affects their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is considered to act as a protective factor by increasing the QoL, coping and overall adaptation to difficulties related to caregivers 11 . The QoL involves the individuals' subjective perceptions about their role in life, based on their culture and system of values 28 . It is a multidimensional and complex concept that encompasses several dimensions 28 .…”
mentioning
confidence: 99%
“…The QoL involves the individuals' subjective perceptions about their role in life, based on their culture and system of values 28 . It is a multidimensional and complex concept that encompasses several dimensions 28 . It seems that resilience helps caregivers maintain their mental and physical Table 3.…”
mentioning
confidence: 99%
“…13 A sobrecarga percebida pelo cuidador de tais demandas também tem se mostrado como um relevante preditor de saúde do mesmo. A sobrecarga foi associada com menor qualidade de vida do cuidador, 14 ansiedade e sintomas depressivos. 15 Alta tensão do papel também foi conectada a maior mortalidade.…”
Section: Introductionunclassified